2011
DOI: 10.1177/0003319711425175
|View full text |Cite
|
Sign up to set email alerts
|

Serum Bilirubin Level is Negatively Correlated With Disease Progression of Peripheral Arterial Disease

Abstract: We determined whether low bilirubin level is a risk factor for peripheral arterial disease (PAD). We recruited 318 patients with PAD and 100 healthy volunteers. Patients were divided into 4 groups by the Fontaine classification for PAD, namely, group 1 (grade 1, n = 4); group 2 (grade 2, n = 114), group 3 (grade 3, n = 164), and group 4 (grade 4, n = 36). Total bilirubin (T-BIL), direct bilirubin (D-BIL), and indirect bilirubin (I-BIL) levels were compared using stepwise multiple regressions adjusted for selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
(55 reference statements)
1
17
0
Order By: Relevance
“…The largest of these studies analysed 7,075 individuals from the National Health and Nutrition Examination Survey, and reported that increased bilirubin levels were associated with a reduced prevalence of PAD [19]. However, hard clinical endpoints were not explored in that and other similar smaller case-control studies [17][18][19][20]. Our study therefore for the first time extends these findings to amputation events.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The largest of these studies analysed 7,075 individuals from the National Health and Nutrition Examination Survey, and reported that increased bilirubin levels were associated with a reduced prevalence of PAD [19]. However, hard clinical endpoints were not explored in that and other similar smaller case-control studies [17][18][19][20]. Our study therefore for the first time extends these findings to amputation events.…”
Section: Discussionmentioning
confidence: 59%
“…Consistent with this notion, case-control studies have reported that individuals with elevated bilirubin levels caused by Gilbert's syndrome have a decreased incidence of atherosclerotic disease compared with normal controls [12,14]. Also, previous studies reported an inverse relationship between bilirubin levels and PAD prevalence [17][18][19][20]. However, the association between bilirubin and the hard clinical endpoint of amputation events has not been reported, to our knowledge.…”
Section: Introductionmentioning
confidence: 60%
“…Earlier researches have demonstrated an inverse correlation between serum bilirubin and the risk of coronary artery disease and decreased antioxidant activity of bilirubin in atherosclerotic lesions [1, 2]. Recent studies have confirmed the correlation between serum bilirubin levels and collateral development in patients with chronic total coronary occlusion [3], peripheral arterial disease [4], amputation events in type-2 diabetes mellitus [5], stroke severity and clinical outcomes [6]. Those results suggested that bilirubin may be a part of a cell defense strategy in those macro- and micro- angiopathies.…”
Section: Introductionmentioning
confidence: 99%
“…PAD is present in up to half of patients with DF and is an independent risk factor for the severity of DF as well as amputation [ 24 ]. Previous studies consistently found that elevated serum bilirubin levels were negatively associated with PAD [ 25 27 ], arterial stiffness [ 10 ], and carotid intima media thickness [ 28 ] in patients with DM. This inverse association is strongly supported by evidence arising from experimental studies.…”
Section: Discussionmentioning
confidence: 99%